6.9k views
1 vote
(11+x)/2-(9x-3)/4 x=3

1 Answer

2 votes

Answer:

(11+X)/2-(9x-3)/4 x=3

subsititute 3 into all x

(11+3)/2-(9*3)-3)/4

first solve the first diviision

2-(9 times 3)-3/4

=2-(27-3)/4

=2-(24)/4

since the "2-" is there, you have to subtract it from 24 before you dividewhich would then be

22/4=5.5(in decimal form)

DON'T forget you have another bracket waiting for you since you were given 3 brackets. bring the first bracket down

2-(9x-3)/4 was solved and we got 5.5, so basically we are "substituting 5.5 into that part of the question)

11+x/5.5

11+3/5.5

14/5.5

=2.54 which is your final answer

Sorry if I went overboard lol.

Explanation:

yes, the answer is 2.54 I believe.

User Raghunandan
by
4.9k points